Organized Illegal Migration as Manifestation of Transnational Criminality and Source of Threats to National Security of Ukraine - O. A. Panchenko (Bulletin of Kharkiv National University of Internal Affairs)
Illegal migration is publicly dangerous, harmful, criminal phenomenon, which really threatens to national security of many countries. The issue of providing the proper state of national security is of greater actuality for Ukraine. Therefore, the issues of scientific analysis of the relationship of migration and national security, making suggestions for the improvement of counteraction to illegal migration, taking into account the threats which it creates, are very important.